GAMBARAN NILAI SGOT DAN SGPT PASIEN TUBERKULOSIS PARU YANG DIRAWAT INAP DI RSUD ARIFIN ACHMAD PROVINSI RIAU TAHUN 2013 - Widya Adriani; Zarfiardy Aksa Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
AbstractTuberculosis (TB) adalah suatu penyakit infeksi menular yang disebabkanoleh kuman Mycobacterium tuberculosis.Tuberculosis ( TB ) is an infectious diseasecaused by Mycobacterium tuberculosis. TB germs attack the organ is mostly thelungs ( pulmonary TB ) , but also can affect almost every organ of the human body .Morbidity and mortality from tuberculosis is a serious problem , especially due to theincidence of side effects due to Anti Tuberculosis ( OAT ) . Side effects The mostserious OAT is hepatotoxic .According to the American Association for the Study of Liver Disease (AASLD ) , establishes that the parameters for determining the presence or absence ofliver damage is to look at the levels of serum glutamic Pyruric transaminase ( SGPT )increased more than three times the upper limit of normal , and serum glutamicoxaloacetic transaminase ( SGOT ) . The purpose of this study to describe the valueof AST and ALT in patients with pulmonary tuberculosis hospitalized in ArifinAchmad Riau Province in 2014 by age , sex and determine the degree ofhepatotoxicity . This study will be conducted at the medical records of the DistrictGeneral Hospital Arifin Achmad Riau Province in January 2015 .The study sample as many as 69 people . The data collected is secondarydata obtained from medical records . The results showed that the largest age groupof patients with pulmonary tuberculosis were aged 40-49 years were 17 ( 24.63 % ) .While the sex of pulmonary TB patients it was found that men were 36 people ( 52.17% ) . Pulmonary TB patients who experienced hepatotoksitas based SGOT was 10people ( 14.49 % ) . Pulmonary TB patients with hepatotoxicity based SGPT value is7 ( 10.14 % ) .pulmonary TB patients with hepatotoxicity based AST highest in the agegroup 40-49 years are 4 people and hepatotoxicity based SGPT highest in the agegroup 18-29 years is 3 people . pulmonary TB patients with hepatotoxicity based ASTsame incidence between men and women respectively 5 people . Pulmonary TBpatients with hepatotoxicity based SGPT most suffered by men is 6 people , whilewomen only 1 person .Keywords: Pulmonary tuberculosis , SGOT , SGPT